Characteristics of hyperparathyroid states in the Canadian multicentre osteoporosis study (CaMos) and relationship to skeletal markers. (1st September 2014) - Berger, C.; Almohareb, O.; Langsetmo, L.; Hanley, D.A.; Kovacs, C.S.; Josse, R.G.; Adachi, J.D.; Prior, J.C.; Towheed, T.; Davison, K.S.; Kaiser, S.M.; Brown, J.P.; et al.
Summary Context PTH is an essential regulator of mineral metabolism; PTH hypersecretion may result in hyperparathyroidism including normocalcaemic, primary and secondary hyperparathyroidism. Objective To examine the characteristics of participants with hyperparathyroid states and the relationship to bone mineral density (BMD). Design and participants A cross‐sectional study of 1872 community‐dwelling men and women aged 35+ years (mostly Caucasian) with available serum PTH from Year 10 Canadian Multicentre Osteoporosis Study follow‐up (2005–07). PTH was determined using a second‐generation chemiluminescence immunoassay. Outcome measures L1‐L4, femoral neck and total hip BMD. Results We established a PTH reference range (2·7–10·2 pmol/l) based on healthy participants (i.e. normal serum calcium, serum 25‐hydroxyvitamin D, kidney function and body mass index, who were nonusers of antiresorptives, glucocorticoids and diuretics and not diagnosed with diabetes or thyroid disease). Participants with PTH levels in the upper reference range (5·6–10·2 pmol/l), representing a prevalence of 10·7%, had lower femoral neck and total hip BMD, by 0·030 g/cm2 [95% confidence interval: 0·009; 0·051] and 0·025 g/cm2 (0·001; 0·049), respectively, than those with levels 2·7–5·6 pmol/l. Participants with normocalcaemic and secondary hyperparathyroidism also had lower total hip BMD than those with levels 2·7–5·6 pmol/l, and CaMos prevalences of normocalcaemic, primary and secondary hyperparathyroidism were 3·3%, 1·4% and 5·2%, respectively. Conclusion We found reduced BMD in participants with accepted hyperparathyroid states but also a notable proportion of other participants that might benefit from having lower PTH levels.